Analisis Empiris Kritis Pengaruh Status Gizi dan Pola Aktivitas Fisik terhadap Tinggi Badan Remaja India: A Critical Empirical Analysis of the Influence of Nutritional Status and Physical Activity Patterns on Height of Indian Youth - Swarnalatha, Swarnalatha; Rajakumaran, Rajakumaran; Akash, Akash; Sethupathy, Sethupathy (Amerta Nutrition, 2025)
Background: Recent research indicates a global trend of increasing average height, while in contrast, the average height in India is experiencing a concerning decline. Although genetic factors account for 60-80% of an individual's final height, environmental and social factors significantly influence it. Objectives: The study objective was to analyze the height of the adults belong to Kerala and Tamil Nadu and its associated determinant factors. Methods: Multi stage sampling method was adopted to identify study samples from two southern districts of India namely Tamil Nadu and Kerala. Different households were randomly selected from the chosen urban areas based on the convenience sampling technique, as per the framed inclusion criteria and included 100 male and female in the age group of 18 to 25 years. A well-structured questionnaire was used to elicit the socio economic, dietary habits, physical activity pattern and anthropometric measurements of the selected samples. SPSS software was used to analyze the data. Pearson Correlation Coefficient and Anova were used to interpret the determining factors.  Results: Pearson’s correlation coefficient analysis (R=0.557, p-value=0.001) and Anova (F=144.8 and p-value<0.001) showed the positive significant relationship between nutritional status and height of the participants and moderate (R=0.311, p-value<0.001), but statistically significant positive relationship between physical activity level and height. Conclusions: The study highlights alarming trends in nutritional status and physical activity among young adults, with both factors showing a significant association with individual height. Addressing these issues is crucial for improving height outcomes in future generations.